The Effect of Interpersonal Communication on Employee Performance: The Mediating role of Teamwork (Study on Banten Provincial General Election Commission) - Made Ayu Setiani; Roni Kambara; Enis Khaerunnisa (PT Larva Wijaya Penerbit, 2026)
Employee performance is a key factor in determining the effectiveness and efficiency of public services. This study examines interpersonal communication and teamwork as factors influencing employee performance. The novelty of this study lies in the use of teamwork as a mediating variable in the relationship between interpersonal communication and employee performance. This study employed a quantitative research approach. The research was conducted at the Banten Provincial General Election Commission, involving a population of 60 employees. Data were collected using a questionnaire measured on a 10-point scale and analyzed using SmartPLS 4. The findings indicate that: (1) interpersonal communication has no significant direct effect on employee performance; (2) interpersonal communication has a positive and significant effect on teamwork; (3) teamwork has a positive and significant effect on employee performance; and (4) teamwork significantly mediates the relationship between interpersonal communication and employee performance.